Characterisation and processing of reinforced PA 6 with halloysite nanotubes (HNT) for injection molding - Fernandez, Angel (Strojniški vestnik, 2013)
The use of nano-scaled reinforcements enchances the mechanical performance of the resulting material and the addition of natural origin nanotubes improve the sustainability and environmental impact of the product. The present work describes the preparation, characterization and processing of nanocomposites based on thermoplastic Polyamide 6 and Halloysite nanotubes (HNT). The nanocomposites were prepared in several stages and the results ensure the final application at industrial scale. The first formulation was a high concentration of Halloysite nanotubes (up to 30% weight content) made with a twin screw extrusion compounder which was used as a masterbatch. Application materials were obtained reducing the masterbatch in raw PA 6 down to 3 or 6% of HNTs weight content. In this stage the influence of use or not an extruder-compounder was analyzed. Finally, a low cost preparation and sustainable development technique as injection moulding was applied to obtain test parts of all developed materials.
Keywords: brizganje; compounding; halloysite nanotubes; halojzitne nanocevke; injection moulding; kompaundiranje; nanocomposites; nanokompoziti